THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL SELF-EFFICACY, FINANCIAL TECHNOLOGY, AND RISK TOLERANCE ON INVESTMENT DECISION - Ni Kadek Tiyas Intan Cahyani; Luh Gede Sri Artini (Adisam Publisher, 2026)
The development of capital markets and the increasing accessibility of digital investment platforms have encouraged greater participation of Generation Z in investment activities. Generation Z utilizes various technology-based investment platforms to conduct transactions and obtain information about diverse investment instruments. Investment decisions are crucial as they determine how investors select investment instruments that align with their financial goals and risk tolerance. Appropriate decisions enable investors to manage funds more optimally and minimize potential losses in investment activities. The phenomenon of digital investment growth and the increasing participation of Generation Z in the capital market highlights the need to examine the factors influencing investment decisions among Generation Z investors. This study aims to analyze the influence of financial knowledge, financial self-efficacy, financial technology, and risk tolerance on investment decisions. The population of this study consists of Generation Z investors who are members of the Semi-Autonomous Body of the Capital Market Study Group of the Faculty of Economics and Business, Udayana University, in the 2025 period. The sample size was determined using the Slovin formula, resulting in 116 respondents. Data were collected through questionnaires distributed via Google Forms. This research employs a quantitative approach using Partial Least Squares (PLS) as the analytical tool. The results indicate that financial knowledge, financial self-efficacy, financial technology, and risk tolerance are at a high level, which contributes to a higher capability in making investment decisions.